Religion, Political Actors, and Democratization: The Turkish Case - Ozzano, Luca (Politics and religion, 2014)
This article is part of a special issue on the five Muslim democracies. It aims at understanding the role played by religion, and particularly by religiously oriented actors, in Turkey's democratization processes. The first section analyzes the different theoretical approaches to the role of religion in democratization. The second section analyzes the different phases of Turkey's political history since the 1980 coup, taking into account both democratization processes and the role played by religious actors in the political system, and trying to understand the possible relations between the two phenomena.